Sheikh Al - Sadouk Messengers - Shammam, Fatima Kazem (International Journal of Psychosocial Rehabilitation, 2020)
The Noble Sunnah is a source of Islamic legislation parallel to the Holy Quran. Any expression with the Holy Quran in one line in the event of the news was true. The noble Sunnah of the Prophet (peace and blessings of Allaah be upon him) speaks of the Islamic rulings and explains this to him. (1) But the year has been subjected to several setbacks since the death of the Great Prophet where it was subjected to the situation and deception and other factors leading to poor speech (2) However, our scholars have betrayed the fact that the Prophet (peace and blessings of Allaah be upon him) Help them and write, save and revise the Hadith (3) of everything It is not true and unadorned. Among these scholars, Shaykh al-Saduq (the Holy of Holies) is the one who wrote the hadiths and classified them according to the jurisprudential issues and stripped the weak and took the correct one. Knowledge and famous and considered by the scientists of men and the expression of his messages is correct.